2019
DOI: 10.22452/mojem.vol7no4.2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of School Related Attributes on Job Satisfaction: A Cross-Sectional Study on School Teachers in Nepal

Abstract: Job satisfaction among school teachers is considered to be one of the crucial aspects in the arena of educational leadership and organizational behaviour. In addition, the question of if school associated attributes contribute to school settings has become a hot cake in the present context. Amidst this, the study aims to examine the job satisfaction of school teachers across their school related attributes. For achieving this purpose, a cross-sectional survey was employed embracing post-positivist paradigm amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The study also found that teacher job satisfaction was low regarding salary. Shrestha (2019) found a positive relationship between job satisfaction and teacher attributes such as years of service, type of service, appointment, and education. However, Shresta's (2019) findings also reported no significant difference between job satisfaction and type of institution.…”
Section: Introductionmentioning
confidence: 92%
“…The study also found that teacher job satisfaction was low regarding salary. Shrestha (2019) found a positive relationship between job satisfaction and teacher attributes such as years of service, type of service, appointment, and education. However, Shresta's (2019) findings also reported no significant difference between job satisfaction and type of institution.…”
Section: Introductionmentioning
confidence: 92%
“…It is a meaningful results of evaluating employee performance in an organization (Langton et al, 2016). The employee motivation is the inner force continually associated with job satisfaction (Shrestha, 2019). In the school setting, JS is a topic that always gets attention because when teachers are not comfortable with their job, it is hard to achieve optimum results (Sembiring & Purba, 2019).…”
Section: Organizational Culture (Oc)mentioning
confidence: 99%
“…In the context of Nepal, a very nominal study was done concerning the commitment of school teachers. Though several studies were completed concerning the job satisfaction of teachers (Shrestha, 2019a;Shrestha, 2019b), the study concerning teachers' commitment is lacking. This study can add one brick for further study of this concern.…”
Section: Influence Of Demographic Variables On Teachers' Commitmentmentioning
confidence: 99%